6 GHz electromagnetic wave guiding along a femtosecond laser plasma filament. Issue 3 (4th November 2019) - Liu, Yang; Chen, Zongsheng; Cheng, Li; Sun, Ke; Shi, Jiaming
Abstract: To study the electromagnetic (EM) wave guiding performance of the plasma filament generated by the intense femtosecond (fs) laser pulse, a 3D physical model of the wave‐plasma interaction is built and discussed with the commercial simulation software XFDTD. Then, an experiment is conducted to verify the EM wave guiding performance of the fs laser plasma filament. Our investigation illustrates that the 6 GHz EM wave can propagate along the fs plasma filament, making the EM field enhance out of the rectangular waveguide and attenuate in the rectangular waveguide. Besides, the filament can cause 4.74 dB enhancement of the wave energy relative to freely propagating the signal. Furthermore, the experimental result indicates that the guiding performance of the plasma filament on the TE polarization wave is better than that on the TM one, which is consistent with the theoretical result. For TE polarization wave, the plasma filament can reduce the microwave signal in the waveguide, which is lesser than that of the Cu wire in the experiment. The research results confirm that the fs laser plasma filament can guide the EM wave with a better performance relative to freely propagating the signal.